1983
DOI: 10.1007/bf00165712
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histochemical evaluation of glycosaminoglycans in brain tumors induced in rats by nitrosourea derivatives

Abstract: The occurrence, distribution and concentration of GAGs in ENU and MNU experimental brain tumors induced in the rat are reported. GAGs have been histochemically studied by Alcian Blue methods; they have been quantified and qualitatively evaluated by electrophoresis of brain extracts. The pattern of GAGs in normal rats is consistent with the data of the literature. No GAG accumulation precedes the tumor development. Early neoplastic proliferations, oligodendroglial and mixed glial microtumors are strongly alcian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The GFAP antibody has received mixed but generally negative reviews for this purpose (3,7,19,20,23 (3,23,36), S-100, and vimentin (7,24,27 …”
Section: Methodsmentioning
confidence: 99%
“…The GFAP antibody has received mixed but generally negative reviews for this purpose (3,7,19,20,23 (3,23,36), S-100, and vimentin (7,24,27 …”
Section: Methodsmentioning
confidence: 99%
“…In part the aggressive nature of malignant brain tumors might be attributed to the brain's unique composition with a relatively low content of fibrous proteins, balanced by very high levels of GAGs. These highly polar and negatively charged molecules tend to attract and bind water, and brain ECM consists mostly of linear chains of heparan sulfates, chondroitin sulfates, keratan sulfates, and HA (Margolis et al, 1975 ; Mauro et al, 1983 ) that can aggregate or attach to other ECM components. There are several lines of evidences that GAGs play an important role in brain malignancies, although the biochemical aspects of GAG-induced signaling is less well-understood than are signals arising from activation of integrins by protein fibers of the ECM.…”
Section: Mechanosensing By Transformed Glial Cellsmentioning
confidence: 99%
“…They were found to be associated with vessel walls and cytoplasmic membranes of tumor cells, in an inverse relationship with dedifferentiation [ 73 , 74 ]. They were also variably distributed, especially in regressive events [ 75 , 76 ], and they showed a particular behavior in ENU transplacentally induced rat brain tumors [ 77 , 78 , 79 ]. In particular, Alcian blue positivity for CS was found in isomorphic ENU oligodendrogliomas, and only in the peripheral part of polymorphic gliomas [ 77 ], in agreement with recent NG2/CSPG4 findings [ 72 ].…”
Section: Ng2 /Cspg4 In Gliomasmentioning
confidence: 99%
“…They were also variably distributed, especially in regressive events [ 75 , 76 ], and they showed a particular behavior in ENU transplacentally induced rat brain tumors [ 77 , 78 , 79 ]. In particular, Alcian blue positivity for CS was found in isomorphic ENU oligodendrogliomas, and only in the peripheral part of polymorphic gliomas [ 77 ], in agreement with recent NG2/CSPG4 findings [ 72 ]. The latter authors, very interestingly, could not obtain neurospheres (NSs) from low-grade tumors, but they observed that after irradiation, surviving cells were NG2/CSPG4+; the stem cell hypothesis of ENU gliomas was, therefore, considered to be very unlikely.…”
Section: Ng2 /Cspg4 In Gliomasmentioning
confidence: 99%